2019
DOI: 10.1245/s10434-019-07741-w
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Residual Cancer Burden as Prognostic Factor for Breast Cancer Patients After Neoadjuvant Therapy

Abstract: Background. Assessing the residual cancer burden (RCB) predictive performance, the potential subgroup effects, and time-dependent impact on breast cancer patients who underwent neoadjuvant therapy in a developer's independent cohort is essential for its usage in clinical routine. Methods. Between 2011 and 2016, the RCB scores of 184 female breast cancer patients were prospectively collected, and subsequent clinicopathological and follow-up data were obtained retrospectively. Recurrence-free survival (RFS), ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 54 publications
(81 reference statements)
2
24
0
3
Order By: Relevance
“…Our data suggest that regrowth of potentially resistant tumor cell populations after NAC may increase RCB score after 6 weeks, and may mediate the observed association of TTS with recurrence and survival. It should be noted that Müller and Symmans have shown that the prognostic impact of changes in the RCB score within RCB classes is low 8,9 . While the increase in RCB score associated with TTS >6 weeks may not be relevant to patients destined to have RCB scores on the low end of Class‐I or Class‐II, patients on the higher end of RCB class cutoffs may experience “upstaging” to a higher RCB class with longer TTS intervals, particularly beyond 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that regrowth of potentially resistant tumor cell populations after NAC may increase RCB score after 6 weeks, and may mediate the observed association of TTS with recurrence and survival. It should be noted that Müller and Symmans have shown that the prognostic impact of changes in the RCB score within RCB classes is low 8,9 . While the increase in RCB score associated with TTS >6 weeks may not be relevant to patients destined to have RCB scores on the low end of Class‐I or Class‐II, patients on the higher end of RCB class cutoffs may experience “upstaging” to a higher RCB class with longer TTS intervals, particularly beyond 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, RCB has been determined to be prognostic for 10-year relapse-free survival rates for multiple patient cohorts treated with different NACTs including fluorouracil, doxorubicin, and cyclophosphamide (FAC), paclitaxel with FAC, and trastuzumab with sequential paclitaxel and fluorouracil, epirubicin and cyclophosphamide. RCB classification was prognostic for TNBC, HR + /HER2and HER2 + phenotypes independent of other prognostic factors [62,63]. While patients with an RCB score 3 have an extremely high risk of tumor recurrence, the risk is lower but still substantial for patients with an RCB score 1-2.…”
Section: Siah As a New Therapy-responsive And Prognostic Biomarker In Breast Cancermentioning
confidence: 92%
“…In a previous study, we validated RCB as an independent prognostic factor for breast cancer patients' survival after neoadjuvant therapy in a single institutional study [13]. The primary objective of the present analyses was to validate these findings in a larger cohort of breast cancer patients, as measured by five-year recurrence-free survival.…”
Section: Introductionmentioning
confidence: 69%
“…We extended our previously published validation study on the prognostic value of RCB score [13] by analyzing 367 breast cancer patients who underwent neoadjuvant treatment at the Division of Oncology, Department of Internal Medicine, Medical University of Graz between 2011 and 2020. The ethics committee of the Medical University of Graz (ethical approval number 31-212 ex 18/19) approved the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation